Pengaruh Pendekatan Pembelajaran Aptitude Treatment Interaction (ATI) Terhadap Hasil Belajar Siswa pada Materi Sistem Pencernaan Kelas VIII SMP Negeri 23 Makassar - Latief, Andi Rini Yanti; Maulana, Andi; Hamansah, Hamansah; Syahriani, Syahriani; Hasanah, Ummul (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of the Aptitude Treatment Interaction (ATI) learning approach on student learning outcomes in the digestive system material for eighth grade students at SMP Negeri 23 Makassar. The study used a quasi-experimental method with a nonequivalent control group design. The study population consisted of 341 eighth grade students, with a sample of 76 students selected purposively and divided into experimental and control groups. Data were collected through learning outcome tests administered at the pre-test and post-test stages to measure improvements in student understanding. In addition, documentation was used to reinforce the research findings. Data analysis was performed using prerequisite tests (normality and homogeneity tests) and the Independent Samples T-Test using statistical software. The results showed that the average learning score of students in the experimental class was 84.13, while in the control class it was 81.76. Hypothesis testing showed a significant difference between the two groups (Sig. < α = 0.001). Based on these findings, it can be concluded that the ATI approach is effective in improving student learning outcomes in digestive system material